Direct effects of glucose, insulin, GLP-1, and GIP on bulbospinal neurons in the rostral ventrolateral medulla in neonatal wistar rats. (6th March 2017) - Oshima, Naoki; Onimaru, Hiroshi; Matsubara, Hidehito; Uchida, Takahiro; Watanabe, Atsushi; Imakiire, Toshihiko; Nishida, Yasuhiro; Kumagai, Hiroo
Highlights: Low-level glucose and insulin increased the activities of the bulbospinal RVLM neurons. GLP-1 and GIP decreased the activities of the bulbospinal RVLM neurons. The presence of transporter of GLUT3 and receptors of insulin, GRP-1 and GIP were demonstrated histologically. Hypoglycemia cause high BP by stimulating bulbospinal RVLM neurons via its specific transporters on these neurons. Hyperinsulinemia and reduction in GLP-1 or GIP cause high BP by activating RVLM neurons via their own receptors. Abstract: Although patients with diabetes mellitus (DM) often exhibit hypertension, the mechanisms responsible for this correlation are not well known. We hypothesized that the bulbospinal neurons in the rostral ventrolateral medulla (RVLM) are affected by the levels of glucose, insulin, or incretins (glucagon like peptide-1 [GLP-1] or glucose-dependent insulinotropic peptide [GIP]) in patients with DM. To investigate whether RVLM neurons are activated by glucose, insulin, GLP-1, or GIP, we examined changes in the membrane potentials of bulbospinal RVLM neurons using whole-cell patch-clamp technique during superfusion with various levels of glucose or these hormones in neonatal Wistar rats. A brainstem–spinal cord preparation was used for the experiments. A low level of glucose stimulated bulbospinal RVLM neurons. During insulin superfusion, almost all the RVLM neurons were depolarized, while during GLP-1 or GIP superfusion, almost all the RVLM neurons were hyperpolarized. Next, histological examinations were performed to examine transporters for glucose and receptors for insulin, GLP-1, and GIP on RVLM neurons. Low-level glucose-depolarized RVLM neurons exhibited the presence of glucose transporter 3 (GLUT3). Meanwhile, insulin-depolarized, GLP-1-hyperpolarized, and GIP-hyperpolarized RVLM neurons showed each of the respective specific receptor. These results indicate that a low level of glucose stimulates bulbospinal RVLM neurons via specific transporters on these neurons, inducing hypertension. Furthermore, an increase in insulin or a reduction in incretins may also activate the sympathetic nervous system and induce hypertension by activating RVLM neurons via their own receptors.